Production of Class II MHC Proteins in Lentiviral Vector‐Transduced HEK‐293T Cells for Tetramer Staining Reagents. Issue 2 (4th February 2021) - Willis, Richard A.; Ramachandiran, Vasanthi; Shires, John C.; Bai, Ge; Jeter, Kelly; Bell, Donielle L.; Han, Lixia; Kazarian, Tamara; Ugwu, Kyla C.; Laur, Oskar; Contreras‐Alcantara, Susana; Long, Dale L.; et al.
Abstract: Class II major histocompatibility complex peptide (MHC‐IIp) multimers are precisely engineered reagents used to detect T cells specific for antigens from pathogens, tumors, and self‐proteins. While the related Class I MHC/peptide (MHC‐Ip) multimers are usually produced from subunits expressed in E. coli, most Class II MHC alleles cannot be produced in bacteria, and this has contributed to the perception that MHC‐IIp reagents are harder to produce. Herein, we present a robust constitutive expression system for soluble biotinylated MHC‐IIp proteins that uses stable lentiviral vector−transduced derivatives of HEK‐293T cells. The expression design includes allele‐specific peptide ligands tethered to the amino‐terminus of the MHC‐II β chain via a protease‐cleavable linker. Following cleavage of the linker, HLA‐DM is used to catalyze efficient peptide exchange, enabling high‐throughput production of many distinct MHC‐IIp complexes from a single production cell line. Peptide exchange is monitored using either of two label‐free methods, native isoelectric focusing gel electrophoresis or matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometry of eluted peptides. Together, these methods produce MHC‐IIp complexes that are highly homogeneous and that form the basis for excellent MHC‐IIp multimer reagents. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Lentivirus production and expression line creation Support Protocol 1 : Six‐well assay for estimation of production cell line yield Support Protocol 2 : Universal ELISA for quantifying proteins with fused leucine zippers and His‐tags Basic Protocol 2 : Cultures for production of Class II MHC proteins Basic Protocol 3 : Purification of Class II MHC proteins by anti‐leucine zipper affinity chromatography Alternate Protocol 1 : IMAC purification of His‐tagged Class II MHC Support Protocol 3 : Protein concentration measurements and adjustments Support Protocol 4 : Polishing purification by anion‐exchange chromatography Support Protocol 5 : Estimating biotinylation percentage by streptavidin precipitation Basic Protocol 4 : Peptide exchange Basic Protocol 5 : Analysis of peptide exchange by matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry Alternate Protocol 2 : Native isoelectric focusing to validate MHC‐II peptide loading Basic Protocol 6 : Multimerization Basic Protocol 7 : Staining cells with Class II MHC tetramers